T. H. Green, Lectures on the Principles of Political Obligation and the Other Writings, ed. P. Harris — J. Morrow, 1986 - Czarnota, Adam (Czasopismo Prawno-Historyczne, 1989)
Recenzja: T. H. Green, Lectures on the Principles of Political Obligation and the Other Writings (ed. Paul Harris i John Morrow), Cambridge University Press, Cambridge 1986,